Pelatihan Pembuatan Nugget Sayur Sebagai Alternatif Pendapatan Ibu Rumah Tangga Di Desa Bunder Jatiluhur Purwakarta - Ayuningtias, Neng Astri; Anjelli, Putri; Rohmat, Siti (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
PKM activities training in making nuggets with the addition of vegetables in Bunder Village as a means of providing information on how to make vegetable nuggets which can be used as a business field for housewives. This activity aims to provide education on how to make vegetable nuggets to increase the income of housewives in Bunder Village. This community service activity uses socialization, training and direct assistance methods. The results of this PKM can be concluded that the community service activities that have been carried out well and smoothly, the vegetable nugget making program provides a very useful understanding for the people of Bunder Village, because it can be made as a home business for housewives that is easy to practice. In addition, the village will provide business capital for mothers who want to do business but have limited business capital.